Antidepressant actions of ketamine: from molecular mechanisms to clinical practice. (February 2015) - Monteggia, Lisa M; Zarate, Carlos
Highlights: Ketamine elicits a rapid antidepressant response in depressed individuals. Blockade of NMDA receptors inhibits eEF2K desuppressing BDNF and leading to an increase in synaptic plasticity. Some glutamatergic blockers also elicit antidepressant effects although they are not as robust and durable as ketamine. Predictive biomarkers to ketamine treatment are being explored. Abstract : In the past decade the emergence of glutamate N-methyl-d -aspartate (NMDA) receptor blockers such as ketamine as fast-acting antidepressants fostered a major conceptual advance by demonstrating the possibility of a rapid antidepressant response. This discovery brings unique mechanistic insight into antidepressant action, as there is a substantial amount of basic knowledge on glutamatergic neurotransmission and how blockade of NMDA receptors may elicit plasticity. The combination of this basic knowledge base and the growing clinical findings will facilitate the development of novel fast acting antidepressants.